ANALYSIS OF ACTIVITY-BASED COSTING IN PRODUCTION PROCESSES: A CASE STUDY - Boongun, Niparat; Inthawongse, Choat; Khanongnuch, Thanida; Muangwai, Alongkorn; Saensamran, Thanthap; Keawsaard, Thippawan; Phetthong, Thiwawan; Pongpaw, Pantisa (วารสารวิชาการเทคโนโลยีอุตสาหกรรมและวิศวกรรม มหาวิทยาลัยราชภัฏพิบูลสงคราม, 2025)
This project aims to study the production processes of Vietnamese pork sausage (Moo Yor), fermented pork (Naem), and Chinese sausage (Kun Chiang) in order to analyze production costs and identify unnecessary activities within the factory that could be reduced. The study began with data collection from Supattra Products Ltd., applying activity-based costing (ABC) to calculate actual production costs and eliminate non-essential expenses. The findings indicate that the production costs-comprising raw materials, labor, and consumables-exceed the current selling prices. This is likely due to the company not accounting for other cost factors such as machinery depreciation and miscellaneous consumables. The unit costs per product are as follows: Moo Yor (90g, 140g, 470g) at 8.43, 13.33, and 44.10 baht respectively; Naem (300g) at 34.28 baht; and Kun Chiang (500g) at 58.10 baht. Moo Yor in all sizes shows the highest production cost. Currently, the selling prices of Moo Yor do not reflect the actual costs incurred. Through cost analysis of Supattra Products Ltd., the study identified cost-generating activities in the production of Moo Yor, Naem, and Kun Chiang. This led to recommendations for setting product prices that align with actual production costs.